Globo Rural : as estratégias da TV aberta para conquistar a audiência da agricultura familiar - Cunha, Ricardo Ramos Carneiro da (2015)
This dissertation has as its theme the specialized journalism in the Brazilian broadcast television. The overall objective is to research the strategies of the Globo Rural Diário (GRD) to meet and attract the audience of the family farming, understood by us as the preferencial audience of this program. Adopted as the research focus the program in Rede Globo, which for 14 years has led information to the farmers, having the part of the corpus of this study, the investigation from the systematic content analysis by Bardin (2011). The theoretical framework that defines and contextualizes the family farming is grounded by the authors such as Ploeg (2008) and Silva (2002). The ideas of participatory and dialogic communication model of Bordenave (2011) and Freire (1977), precursors in the study of the rural communication, help to understand the relationship of media and the countryside. From the news presented in the program, this study concludes that the GRD maintained a close relationship with family farmers through the selection of newswhortiness, as well as addressing operators who were loyal to the public, although it often was represented in a stereotyped way. In the theoretical framework of this study were also used the concepts of Wolton (1996), Bucci (2004), Erbolato (1981), Ferrés (1998), Souza (2004), Gomes (2011), Marcondes Filho (2009), Alsina (2009), Traquina (2008) and Wolf (2012).